EFEKTIFITAS ALOKASI DANA DESA (ADD) DAN KEMISKINAN DI PROVINSI SUMATERA SELATAN - Azwardi Azwardi; Sukanto Sukanto (Jurnal Ekonomi Pembangunan, 2014)
This study aims to acquire an overview of the distribution of funds allocation in rural South Sumatra Province, and its relationship with the level of poverty. Data used time series data from 2006 to 2012. Statistical method used is qualitative and quantitative, with a simple regression model. The results showed that the Rural Fund Allocation (ADD) is not in accordance with the applicable provisions. When viewed from the extended to the year 2012 no one ever meets the applicable provisions (at least 10% of funds for revenue minus expenses plus tax officials). However, the district has been doing distributing ADD showed increasing, when in 2006 of 35.71%, increasing to 90% in the year 2012 This is due, government regulations on the ADD does not provide sanctions for non-distribution returning ADD. When an area it has not been able to estimate ADD provincial and central government can do strictly the sanctions. Simple regression results indicate a negative influence on the level of poverty among ADD, as well as the simulation results with ADD at least 10% of the poverty even show a negative correlation. Keywords: Distribution of Funds Allocation, Poverty